STRATEGI KOMUNIKASI PENGASUH DALAM MEMBENTUK KARAKTER RELIGIUS ANAK PADA PANTI ASUHAN DHARMA WIDYA KUMARA KELURAHAN KUBU KABUPATEN BANGLI - Ni Komang Ayu Puspawati; Dewa Ketut Wisnawa; I Made Arsa Wiguna (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
Based on this background, researchers are interested in researching related to "Caregiver Communication Strategies in Forming the Religious Character of Children at the Dharma Widya Kumara Orphanage, Kubu Village, Bangli Regency", with the formulation of the problem, namely 1) What is the communication strategy used by caregivers in shaping the religious character of children? 2) What are the obstacles and efforts made by caregivers in using communication strategies to shape the religious character of children? 3) What is the impact of the communication strategy used by caregivers in shaping the religious character of children? The theory used in this research is interpersonal communication theory, communication barrier theory, S_O_R (Stimulus-Organism-Response) theory. This study uses a qualitative approach. This type of data collection is qualitative from primary and secondary data sources. Data collection techniques used are observation, interviews, documentation.The findings of the research are: 1) The communication strategies applied by caregivers in shaping the religious character of children at the Dharma Widya Kumara Orphanage, Kubu Village, Bangli Regency are persuasive communication strategies,coercive communication strategies and redundancy (reputation) communication strategies. 2) Obstacles in implementing communication strategies by caregivers in forming the religious character of children at the Dharma Widya Kumara Orphanage, Kubu Village, Bangli Regency, have internal and external obstacles. 3) The impacts arising from the communication strategy applied by caregivers in shaping the religious character of foster children at the Dharma Widya Kumara Orphanage, Kubu Village, Bangli Regency are: changes in the quality of children from the cognitive aspect, changes in the quality of children from the affective aspect, changes in the quality of children from the psychomotor aspect.